Prevalence and survival associated with pulmonary hypertension after mitral valve replacement: National echocardiography database of Australia study. (17th October 2022) - Collins, Nicholas; Sugito, Stuart; Davies, Allan; Boyle, Andrew; Sverdlov, Aaron; Attia, John; Stewart, Simon; Playford, David; Strange, Geoff
Abstract: The specific prevalence and outcome of pulmonary hypertension after mitral valve replacement (MVR) is not well documented. The aim of the study was to determine the prevalence and prognostic impact of pulmonary hypertension after MVR. In addition, we sought to determine the threshold of mortality risk according to echocardiography derived pulmonary pressures and those echocardiographic characteristics that are associated with increased mortality. Using the National Echocardiography Database of Australia, patients who had undergone MVR were identified with estimated right ventricular systolic pressure (eRVSP) assessed and linked to patient mortality during mean follow up of 1917 days. Classification and regression tree analysis was used to identify the most powerful predictors of mortality. A total of 10, 994 patients who had undergone echocardiography following MVR (mean age 65.2 ± 16, 44.8% women) were studied (mean follow‐up 1917 days). The prevalence of PH (defined as eRSVP ≥40 mmHg) was 64.1% (7042/10, 994). Severe PH (eRVSP ≥60 mmHg) was seen in 42.3% (4671/10, 994). Mortality in individuals with PH was greater than amongst individuals without PH (41.1% vs. 26.3%). Age, tricuspid regurgitation and left ventricular dysfunction were also associated with mortality. There is a high prevalence of PH after MVR which confers an adverse prognosis. Improved therapeutic approaches to mitral valve disease and the subsequent development of PH are essential.